HANDWRITTEN COPIES OF ALISHER NAVOI'S DIVANS WRITTEN IN THE 19TH CENTURY (BASED ON THE FUND OF THE STATE LITERARY MUSEUM) - qizi, Mahmudova Mahliyo Ma’rufjon (PT. Antis International Publisher, 2024)
In this article, brief information is given about the manuscript copies of the 19th century divans among the manuscript works belonging to Alisher Navoi in the catalog of manuscripts of the Alisher Navoi State Literature Museum of the Academy of Sciences of the Republic of Uzbekistan. In the article, twenty-seven manuscripts belonging to the 19th century were selected from the museum fund, and information was given about their brief description, some of their shortcomings, and their characteristics.